Challenging national narratives in Palestine/Israel: interconnections between past and present - Daniele, G. (Quest. Issues in Contemporary Jewish History, 2013)
Taking account of the original meaning of ‘inextricability’ among Arabs and Jews, Palestinians and Israelis, the paper aims at exploring whether joint Palestinian and Israeli Jewish viewpoints should be considered as a feasible scenario. With the purpose of deconstructing conventional approaches towards resolution of the Israeli-Palestinian conflict, the leitmotiv of the study is centered on the critical examination of the most prominent intellectual debates and historic examples that have challenged a daily reality developed around fear and hostility directed against the so-called Other. In this way, whilst recognizing a number of failures experienced by the majority of joint initiatives, I suggest how this type of political perspective has made it possible for potentially useful initiatives to emerge within the worsening context of military occupation and conflicting narratives.